Analysis Of Modified Technology Acceptance Model (TAM) In E-Learning Platform For School Administrators Training - Abdul Halim, Ahmad Hanizar (2017)
This thesis aims to explore the school administrators’ technology acceptance of an e-Learning Platform (eLP) associated to the National Professional Qualification Educational Leadership (NPQEL) training programme in Institut Aminuddin Baki (IAB). In order to understand what drives the school administrators to use the etraining system in the training, this study proposes a conceptual framework that modifies the standard Technology Acceptance Model (TAM) to include the computer self-efficacy motivation, organizational policy and incentive and technical support as external variables.